Investigating the antioxidant, anti-inflammatory and anti-cancer potential of Ononis natrix L. with phytochemical analyses - Ahmed M M, Youssef; Noha E A, Mohamed; Khaleel R, Abuawad; Mohammad A, ‎Alkhojah; Rasha M, ‎Hussein (Plant Science Today, 2025)
Ononis natrix L. (O. natrix) belongs to Fabaceae family and ?grows on the coast of Mediterranean Sea. The current study aims to investigate the antioxidant, anti-inflammatory and anti-cancer activities of the methanolic extract of O. natrix and identify the phytochemical constituents responsible for these effects. Gas chromatography-mass spectrometry (GC-MS) was employed to characterize the phytochemicals found in the extract. The human red blood cells (RBCs) membrane stabilization method, ferric reducing antioxidant power (FRAP), total antioxidant capacity (TAC), 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging assay and MTT viability assay were used to investigate the anti-inflammatory, antioxidant and anti-cancer activities. The results showed that methyl stearate (39.48%) and hexadecanoic acid, methyl ester (35.61%) were the most relatively abundant phytochemicals identified by GC-MS. The % hemolysis inhibition for RBC membrane achieved by O. natrix extract was 99.6 ± 1% versus that by indomethacin was 99.9 ± 0.6%. Additionally, the DPPH radical scavenging activity of O. natrix extract versus ascorbic acid was 97 ± 0.3% and 98 ± 0.2%, respectively. The O. natrix extract showed a lower anti-cancer activity against DLD-1 cells (IC50 = 57.13±4.9 µg/mL), MCF-7 cells (IC50 = 96.69±6.2 µg/mL) and A549 cells (IC50 = 126.63±10.4 µg/mL), when compared with the anti-cancer drug; Cisplatin. Therefore, O. natrix extract showed significant anti-inflammatory, antioxidant and anti-cancer properties, which could be attributed to methyl stearate and hexadecanoic acid, methyl ester constituents.